THE INTEGRATIVE THEMATIC LEARNING MODEL IN CURRICULUM 2013 IN MADRASAH IBTIDAIYAH - Sanusi Sanusi (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2017)
This paper comes as a reflection as well as aims to describe the concept and implementation of thematic-integrative learning in Madrasah Ibtidaiyah in the curriculum 2013. Basically the idea of the concept of thematic-integrative learning model in the curriculum 2013 is in response to the dynamics of education-oriented efforts to improve the quality of education through giving a more meaningful experience to the learners in the learning process that takes place in their educational environment. The integration effort is done through a learning approach that combines the various competencies from various subjects into specific themes that become a unified whole. Thematic-integrative learning is an approach in learning that is oriented at the stage of the development of learners, especially at the level of Madrasah Ibtidaiyah which in its development still see everything as a whole unity and only able to understand the relationship between the concept simply.